Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

Integrating biodiversity into land-use regulations: Evidence from Swiss municipal plan revisions - Stephanie Schwab Cammarano; Marco Moretti; Rolf Holderegger; Florian Altermatt; Anna M. Hersperger (Urban Forestry & Urban Greening, 2026)

Riparian Forests and Macroinvertebrates Support Multiple Ecosystem Processes Across Temperate and Tropical Streams - Rebecca Oester; Paula M. de Omena; Larissa Corteletti da Costa; Marcelo S. Moretti; Florian Altermatt; Andreas Bruder (Ecosystems, 2026)
Ecosystems are interconnected, and ecological processes frequently transcend the physical boundaries that define them. Fluxes of energy, matter, and organisms not only form important ecosystem processes within but also between ecosystems. However, the role of biological drivers in simultaneously supporting multiple ecosystem processes at the interface between aquatic and terrestrial ecosystems (that is, aquatic-terrestrial ecosystem processes) remains poorly understood, both locally and across regions. To assess the relative importance of riparian forests, detritus consumers and leaf litter mixing on different ecosystem processes of freshwater detrital food webs, we used leaf litter bags to subsidise local terrestrial leaf litter to forested and non-forested headwater stream sites in a temperate and tropical region. We also manipulated macroinvertebrate access and the composition of leaf litter mixtures. We measured three key aquatic-terrestrial ecosystem processes: biomass accrual of aquatic fungi, nitrogen loss, and decomposition rates of local leaf litter. Across both temperate and tropical streams, ecosystem multifunctionality, that is, the simultaneous sustaining of these processes, was positively associated with macroinvertebrates and riparian forests but not with leaf litter mixing. Especially leaf litter nitrogen loss and decomposition rates were consistently higher when macroinvertebrates had access across all leaf litter species. Decomposition rates were also positively associated with the other ecosystem processes. These findings highlight consistent, cross-regional effects of riparian forests and macroinvertebrate detritivores on freshwater detrital food webs. In a rapidly changing world, understanding ecosystem processes in headwater streams demands a holistic view that transcends ecosystem borders and incorporates cross-ecosystem interactions.

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Short-chain PFAS perinatal exposure induces cognitive dysfunction and glial activation in adult rats - G. Foiani; M. Moretti; C. Zanardello; M. Sannia; E. Melchiotti; A. Vitola; F. Gallocchio; L. Lorenzini; L. Giardino; F. Mutinelli; L. Calzà; M. Vascellari (Journal of Comparative Pathology, 2025)

Green roofs harbor different and non-substituting invertebrate communities than surrounding ground-level habitats - Kilian Perrelet; Marco Moretti; Océane Inglard; Florian Altermatt; Lauren M. Cook (Journal of Environmental Management, 2025)

Urbanisation Drives the Decoupling, Simplification, and Homogenization of Aquatic and Terrestrial Food Webs - Kilian Perrelet; Lauren M. Cook; Merin Reji Chacko; Florian Altermatt; Marco Moretti (Ecology Letters, 2025)
Aquatic and terrestrial communities often co‐occur at close distances, enabling biotic interactions across ecosystem boundaries. While such interactions in natural habitats contribute to complex, coupled food webs, their dynamics in engineered and fragmented urban habitats are hardly known. Using environmental DNA metabarcoding and a metaweb approach, we examined food web structure at 54 paired aquatic‐terrestrial sites along an urbanisation gradient in Zurich, Switzerland. We found that urbanisation led to simpler, less connected, and more homogeneous food webs by replacing high‐trophic‐level predators with low‐trophic‐level basal consumers. This shift towards basal consumers, dependent on distinct aquatic or terrestrial basal resources, subsequently weakened the links between aquatic and terrestrial food webs. Conversely, enhancing habitat quantity and landscape connectivity bolstered predator diversity, promoting vertically diverse, connected, complex, and stable food webs. Our findings reveal that while urbanisation can disrupt aquatic‐terrestrial food webs, careful urban habitat planning can enhance biodiversity and food web stability.

Aquatic and terrestrial environmental DNA signals reveal decoupling of blue-green communities along an urbanization gradient - Kilian Perrelet; Lauren M. Cook; Andreas Dietzel; Florian Altermatt; Marco Moretti (Landscape and Urban Planning, 2025)

Mössbauer spectroscopy: a key tool to quantify Fe-speciation and distribution in H2-generating rocks - U. Geymond; K. Loiseau; V. Roche; G. Pasquet; S. Revillon; M. Sougrati; I. Moretti (Applied Geochemistry, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Effects of apples ( Malus domestica ) and their derivatives on metabolic conditions related to inflammation and oxidative stress and an overview of by-products use in food processing - Otávio Simões Girotto; Otávio Oliveira Furlan; Renato Cesar Moretti Junior; Ricardo de Alvares Goulart; Edgar Baldi Junior; Caroline Barbalho-Lamas; Lucas Fornari Laurindo; Sandra M. Barbalho (Critical Reviews in Food Science and Nutrition, 2025)

Disruption of serotonin homeostasis in intestinal organoids provides insights into drug-induced gastrointestinal toxicity - Georgia M. Rouseti; Audrey Fischer; Nicole Rathfelder; Karen Grimes; Annick Waldt; Rachel Cuttat; Sven Schuierer; Sophia Wild; Magali Jivkov; Valerie Dubost; Heiko S. Schadt; Alex Odermatt; et al. (Toxicology, 2025)

Accuracy assessment of the geomorphon approach to detect ecological sites in the Dry Chaco region of Argentina - Rubén D. Coria; Colby Brungard; Amanda L. Vizgarra; Lucas M. Moretti; Guillermo A. Schulz; Darío M. Rodríguez (CATENA, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Floral species evenness is the major driver of wild bee communities in urban gardens - B.A. Rossi Rotondi; J. Casanelles-Abella; S. Fontana; M. Moretti; M. Videla; M.S. Fenoglio (Urban Ecosystems, 2024)

Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

DNA damage in workers exposed to pigment grade titanium dioxide (TiO2) and association with biomarkers of oxidative stress and inflammation - Sa. Bonetta; M. Macrì; M. Acito; M. Villarini; M. Moretti; Si. Bonetta; D. Bosio; G. Mariella; V. Bellisario; E. Bergamaschi; E. Carraro (Environmental Toxicology and Pharmacology, 2024)

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

P16-37: Comparative assessment of hepatic in vitro systems for detection of drug-induced liver injury - F. Schwald; J. Velazquez; B. Fischer; M. Rana; M. Goetschy; K. Kubek; F. Moretti (Toxicology Letters, 2023)

Seyfert-1 galaxies in WINGS and Omega-WINGS - Paola Marziani; Mauro D’Onofrio; Mario Radovich; Alessia Moretti; Bianca M. Poggianti (Advances in Space Research, 2023)

Feline injection-site sarcomas (FISSs): could the assessment of tumour-infiltrating lymphocytes (TILs) help in prog-nostic evaluations? - I. Porcellato; E. Treggiari; V. Gismondi; I. Di Matteo; C. De Feo; G. Moretti; P. Roccabianca; E. Lepri; M. Sforna; C. Brachelente (Journal of Comparative Pathology, 2023)

Sedimentological features of asbestos cement fragments in coastal environments (Taranto, southern Italy) - S. Lisco; I. Lapietra; R. Laviano; G. Mastronuzzi; T. Fracchiolla; M. Moretti (Marine Pollution Bulletin, 2023)

Experimental assessment of an indirect method to measure the post-combustion flue gas flow rate in waste-to-energy plant based on multi-point measurements - G. Bellani; L. Lazzarini; A. Dal Pozzo; S. Moretti; M. Zattini; V. Cozzani; A. Talamelli (Waste Management, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy) - I Lapietra; S Lisco; G Mastronuzzi; S Milli; C Pierri; F Sabatier; G Scardino; M Moretti (Journal of Earth System Science, 2022)

Protective effect of nutraceutical food on the intestinal mucosa of juvenile pacu Piaractus mesopotamicus under high stocking density - Mariana C. F. Pontin; Wiolene M. Nordi; Jéssica Pampolini; Raul Machado-Neto; Débora B. Moretti (Aquaculture International, 2020)

Effects of Maternal Dietary Cottonseed on the Profile of Minerals in the Testes of the Lamb - Helder Louvandini; Egon H. Ieda; Carolina R. Jimenez; Patricia Spoto Corrêa; Debora B. Moretti; Paulo M. T. Lima; Concepta M. McManus; Hudson W. P. Carvalho; Elisabete A. De N. Fernandes (Biological Trace Element Research, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Multisource data integration to investigate one century of evolution for the Agnone landslide (Molise, southern Italy) - M. Del Soldato; A. Riquelme; S. Bianchini; R. Tomàs; D. Di Martire; P. De Vita; S. Moretti; D. Calcaterra (Landslides, 2018)

Accessing Gene Expression in Treatment-Resistant Schizophrenia - Patricia N. Moretti; Vanessa K. Ota; Eduardo S. Gouvea; Mariana Pedrini; Marcos L. Santoro; Fernanda Talarico; Leticia M. Spindola; Carolina Muniz Carvalho; Cristiano Noto; Gabriela Xavier; Elisa Brietzke; Ary Gadelha; et al. (Molecular Neurobiology, 2018)

Claviceps arundinis identification and its role in the die-back syndrome of Phragmites australis populations in central Italy - M. Cerri; L. Reale; C. Moretti; R. Buonaurio; A. Coppi; V. Ferri; B. Foggi; D. Gigante; L. Lastrucci; M. Quaglia; R. Venanzoni; F. Ferranti (Plant Biosystems, 2018)

Monitoring of ochratoxin A and ochratoxin-producing fungi in traditional salami manufactured in Northern Italy - C. Merla; G. Andreoli; C. Garino; N. Vicari; G. Tosi; M. L. Guglielminetti; A. Moretti; A. Biancardi; M. Arlorio; M. Fabbi (Mycotoxin Research, 2018)

Evidence for the involvement of opioid system in the antidepressant-like effect of ascorbic acid - Morgana Moretti; Camille M. Ribeiro; Vivian B. Neis; Luis Eduardo B. Bettio; Priscila B. Rosa; Ana Lúcia S. Rodrigues (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Advanced interpretation of interferometric SAR data to detect, monitor and model ground subsidence: outcomes from the ESA-GMES Terrafirma project - F. Raspini; S. Bianchini; S. Moretti; C. Loupasakis; D. Rozos; J. Duro; M. Garcia (Natural Hazards, 2016)

Histochemical distribution of intestinal enzymes of juvenile pacu (Piaractus mesopotamicus) fed lyophilized bovine colostrum - Débora B. Moretti; Wiolene M. Nordi; Thaline M. P. Cruz; José Eurico P. Cyrino; Raul Machado-Neto (Fish Physiology and Biochemistry, 2014)

Geochemical and isotopic insights into the assembly, evolution and disruption of a magmatic plumbing system before and after a cataclysmic caldera-collapse eruption at Ischia volcano (Italy) - R. J. Brown; L. Civetta; I. Arienzo; M. D’Antonio; R. Moretti; G. Orsi; E. L. Tomlinson; P. G. Albert; M. A. Menzies (Contributions to Mineralogy and Petrology, 2014)

Genetic polymorphisms and traumatic brain injury: the contribution of individual differences to recovery - Starla M. Weaver; Jaclyn N. Portelli; Aileen Chau; Irene Cristofori; Laura Moretti; Jordan Grafman (Brain Imaging and Behavior, 2014)

Habitat connectivity shapes urban arthropod communities: the key role of green roofs - S. Braaker; J. Ghazoul; M. K. Obrist; M. Moretti (Ecology, 2014)
The installation of green roofs, defined here as rooftops with a shallow soil cover and extensive vegetation, has been proposed as a possible measure to mitigate the loss of green space caused by the steady growth of cities. However, the effectiveness of green roofs in supporting arthropod communities, and the extent to which they facilitate connectivity of these communities within the urban environment is currently largely unknown. We investigated the variation of species community composition (β diversity) of four arthropod groups with contrasting mobility (Carabidae, Araneae, Curculionidae, and Apidae) on 40 green roofs and 40 extensively managed green sites on the ground in the city of Zurich, Switzerland. With redundancy analysis and variation partitioning, we (1) disentangled the relative importance of local environmental conditions, the surrounding land cover composition, and habitat connectivity on species community composition, (2) searched for specific spatial scales of habitat connectivity for the different arthropod groups, and (3) discussed the ecological and functional value of green roofs in cities. Our study revealed that on green roofs community composition of high‐mobility arthropod groups (bees and weevils) were mainly shaped by habitat connectivity, while low‐mobility arthropod groups (carabids and spiders) were more influenced by local environmental conditions. A similar but less pronounced pattern was found for ground communities. The high importance of habitat connectivity in shaping high‐mobility species community composition indicates that these green roof communities are substantially connected by the frequent exchange of individuals among surrounding green roofs. On the other hand, low‐mobility species communities on green roofs are more likely connected to ground sites than to other green roofs. The integration of green roofs in urban spatial planning strategies has great potential to enable higher connectivity among green spaces, so that eventually even communities of low‐mobility species become connected. Furthermore, improving the design of green roofs (composition and configuration of vegetation and soil types) could enhance the ecological value, particularly for low‐mobility species.

Selection of Multiple Umbrella Species for Functional and Taxonomic Diversity to Represent Urban Biodiversity - T. SATTLER; G. B. PEZZATTI; M. P. NOBIS; M. K. OBRIST; T. ROTH; M. MORETTI (Conservation Biology, 2014)
Surrogates, such as umbrella species, are commonly used to reduce the complexity of quantifying biodiversity for conservation purposes. The presence of umbrella species is often indicative of high taxonomic diversity; however, functional diversity is now recognized as an important metric for biodiversity and thus should be considered when choosing umbrella species. We identified umbrella species associated with high taxonomic and functional biodiversity in urban areas in Switzerland. We analyzed 39,752 individuals of 574 animal species from 96 study plots and 1397 presences of 262 plant species from 58 plots. Thirty‐one biodiversity measures of 7 taxonomic groups (plants, spiders, bees, ground beetles, lady bugs, weevils and birds) were included in within‐ and across‐taxa analyses. Sixteen measures were taxonomical (species richness and species diversity), whereas 15 were functional (species traits including mobility, resource use, and reproduction). We used indicator value analysis to identify umbrella species associated with single or multiple biodiversity measures. Many umbrella species were indicators of high biodiversity within their own taxonomic group (from 33.3% in weevils to 93.8% in birds), to a lesser extent they were indicators across taxa. Principal component analysis revealed that umbrella species for multiple measures of biodiversity represented different aspects of biodiversity, especially with respect to measures of taxonomic and functional diversity. Thus, even umbrella species for multiple measures of biodiversity were complementary in the biodiversity aspects they represented. Thus, the choice of umbrella species based solely on taxonomic diversity is questionable and may not represent biodiversity comprehensively. Our results suggest that, depending on conservation priorities, managers should choose multiple and complementary umbrella species to assess the state of biodiversity. Selección de Múltiples Especies Paraguas para la Diversidad Funcional y Taxonómica para Representar la Biodiversidad Urbana

Distribution of glyphosate-resistant and glyphosate-susceptible hairy fleabane (Conyza bonariensis) in central California and their phenological development - Anil Shrestha; Katrina M. Steinhauer; Marcelo L. Moretti; Bradley D. Hanson; Marie Jasieniuk; Kurt J. Hembree; Steven D. Wright (Journal of Pest Science, 2014)

Aspergillus section Nigri as contributor of fumonisin B 2 contamination in maize - A.F. Logrieco; M. Haidukowski; A. Susca; G. Mulè; G.P. Munkvold; A. Moretti (Food Additives & Contaminants: Part A, 2014)

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Herbivore species identity mediates interspecific competition between plants - S. Ibanez; M. Bison; S. Lavorel; M. Moretti (Community Ecology, 2013)

Analysis of the PKR-eIF2alpha phosphorylation homology domain (PePHD) of hepatitis C virus genotype 1 in HIV-coinfected patients by ultra-deep pyrosequencing and its relationship to responses to pegylated interferon-ribavirin treatment - F. Bolcic; M. Sede; F. Moretti; G. Westergaard; M. Vazquez; N. Laufer; J. Quarleri (Archives of Virology, 2012)

High-Resolution Fibre-Optic Temperature Sensing: A New Tool to Study the Two-Dimensional Structure of Atmospheric Surface-Layer Flow - Christoph K. Thomas; Adam M. Kennedy; John S. Selker; Ayla Moretti; Martin H. Schroth; Alexander R. Smoot; Nicholas B. Tufillaro; Matthias J. Zeeman (Boundary-Layer Meteorology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Molecular characterization of two distinct strains of blueberry scorch virus (BlScV) in northern Italy - M. Moretti; M. Ciuffo; P. Gotta; D. Prodorutti; P. Bragagna; M. Turina (Archives of Virology, 2011)

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Scanning electron microscopy studies of cuticle micromorphology in Cycas L. (Cycadaceae) - J. E. Mickle; M. Rosaria Barone Lumaga; A. Moretti; P. De Luca (Plant Biosystems, 2011)

Anti-HIV Drugs Nevirapine and Efavirenz Affect Anxiety-Related Behavior and Cognitive Performance in Mice - Pedro R. T. Romão; Joelson C. Lemos; Jeverson Moreira; Gisele de Chaves; Morgana Moretti; Adalberto A. Castro; Vanessa M. Andrade; Carina R. Boeck; João Quevedo; Elaine C. Gavioli (Neurotoxicity Research, 2011)

Spider, bee, and bird communities in cities are shaped by environmental control and high stochasticity - T. Sattler; D. Borcard; R. Arlettaz; F. Bontadina; P. Legendre; M. K. Obrist; M. Moretti (Ecology, 2010)
Spatially organized distribution patterns of species and communities are shaped by both autogenic processes (neutral mechanism theory) and exogenous processes (niche theory). In the latter, environmental variables that are themselves spatially organized induce spatial structure in the response variables. The relative importance of these processes has not yet been investigated in urban habitats. We compared the variance explained by purely spatial, spatially structured environmental, and purely environmental components for the community composition of spiders (Araneae), bees (Apidae), and birds (Aves) at 96 locations in three Swiss cities. Environmental variables (topography, climate, land cover, urban green management) were measured on four different radii around sampling points ( Our results suggest that the anthropogenic structuring of urban areas has disrupted the spatial organization of environmental variables and inhibited the development of biotic spatial processes. The near absence of spatial structure may therefore be a feature typical of urban species assemblages, resulting in urban community composition mainly influenced by local environmental variables. Urban environments represent a close‐knit mosaic of habitats that are regularly disturbed. Species communities in urban areas are far from equilibrium. Our analysis also suggests that urban communities need to be considered as being in constant change to adapt to disturbances and changes imposed by human activities.

Determinants for the conservation of a vulnerable fire-dependent species at its marginal range - M. Moretti; C. Staehli; F. Gillet (Plant Ecology, 2008)

Lipid-lowering drug use in Italian primary care: effects of reimbursement criteria revision - G. Trifirò; M. Alacqua; S. Corrao; S. Moretti; D. U. Tari; M. Galdo; A. P. Caputi; V. Arcoraci (European Journal of Clinical Pharmacology, 2008)

Quantifying functional diversity with graph-theoretical measures: advantages and pitfalls - C. Ricotta; M. Moretti (Community Ecology, 2008)

Identification of severe potential drug-drug interactions using an Italian general-practitioner database - L. Magro; A. Conforti; F. Del Zotti; R. Leone; M. L. Iorio; I. Meneghelli; D. Massignani; E. Visonà; U. Moretti (European Journal of Clinical Pharmacology, 2008)

Viral outcome of simian–human immunodeficiency virus SHIV-89.6P adapted to cynomolgus monkeys - A. Borsetti; S. Baroncelli; M. T. Maggiorella; S. Bellino; S. Moretti; L. Sernicola; R. Belli; B. Ridolfi; S. Farcomeni; D. R. M. Negri; A. Cafaro; B. Ensoli; et al. (Archives of Virology, 2008)

Importance of species abundance for assessment of trait composition: an example based on pollinator communities - F. Bello; J. Lepš; S. Lavorel; M. Moretti (Community Ecology, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Use and safety profile of antiepileptic drugs in Italy - M. L. Iorio; U. Moretti; S. Colcera; L. Magro; I. Meneghelli; D. Motola; A. L. Rivolta; F. Salvo; G. P. Velo (European Journal of Clinical Pharmacology, 2007)

Quality of Primary Food Products as Affected by Climate Change - G. Savoini; V. M. Moretti (Veterinary Research Communications, 2006)

Evaluation of Fusarium solani Hyphae and Conidia Susceptibility to Amphotericin B and Itraconazole: Study of a Clinical Case - A. B. A. Teixeira; M. L. Moretti; P. Trabasso; A. von Nowakonski; F. H. Aoki; A. C. Vigorito; M. Miyaji; K. Nishimura; H. Taguchi; A. Z. Schreiber (Mycopathologia, 2005)

Diagnosis of candidemia by polymerase chain reaction and blood culture: prospective study in a high-risk population and identification of variables associated with development of candidemia - M. S. Moreira-Oliveira; Y. Mikami; M. Miyaji; T. Imai; A. Z. Schreiber; M. L. Moretti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Mainshocks and aftershocks of the 2002 molise seismic sequence, southern Italy - C. Chiarabba; P. De Gori; L. Chiaraluce; P. Bordoni; M. Cattaneo; M. De Martin; A. Frepoli; A. Michelini; A. Monachesi; M. Moretti; G. P. Augliera; E. D'Alema; et al. (Journal of Seismology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Human cryptococcosis: relationship of environmental and clinical strains of Cryptococcus neoformans var. neoformans from urban and rural areas - A.C.N. Delgado; H. Taguchi; Y. Mikami; M. Myiajy; M.C.B. Villares; M.L. Moretti (Mycopathologia, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Mitochondrial DNA Variability in Fusarium Proliferatum (Gibberella Intermedia) - M. Láday; G. Mulè; A. Moretti; Z. Hamari; Á. Juhász; Á. Szécsi; A. Logrieco (European Journal of Plant Pathology, 2004)

Mitochondrial DNA Diversity and Lineage Determination of European Isolates of Fusarium graminearum (Gibberella zeae) - M. Láday; Á. Juhász; G. Mulè; A. Moretti; Á. Szécsi; A. Logrieco (European Journal of Plant Pathology, 2004)

Phaeohyphomycosis Caused by Chaetomium Globosum in an Allogeneic Bone Marrow Transplant Recipient - A.B.A. Teixeira; P. Trabasso; M.L. Moretti-Branchini; F.H. Aoki; A.C. Vigorito; M. Miyaji; Y. Mikami; M. Takada; A.Z. Schreiber (Mycopathologia, 2003)

Relationships between Na + , K + ‐ATPase, sialic acid content and fluidity in rainbow trout density‐separated erythrocytes - E. Salvolini; L. Nanetti; N. Moretti; A. Vignini; D. Martarelli; A. Frontini; A. M. Santroni; G. Falcioni; L. Mazzanti (Journal of Fish Biology, 2002)
A correlation was found between membrane fluidity, sialic acid (SA) content and Na + , K + ‐ATPase activity in the rainbow trout Oncorhynchus mykiss erythrocyte membrane and this suggests that alterations in erythrocyte Na + , K + ‐ATPase activity might be caused by modified membrane fluidity through modified SA content.

Liquefaction and fluidization structures in Messinian storm deposits (Bajo Segura Basin, Betic Cordillera, southern Spain) - P. Alfaro; J. Delgado; A. Estévez; J. Molina; M. Moretti; J. Soria (International Journal of Earth Sciences, 2002)

Applicability of Aspecific Noninvasive Methods for Biomonitoring of Occupational Exposure to Deltamethrin: Preliminary Study Using an Animal Model - M. Moretti; M. Villarini; G. Scassellati-Sforzolini; R. Pasquini; S. Monarca (Archives of Environmental Contamination and Toxicology, 1997)

Fusarium Proliferatum from Date Palm, in Saudi Arabia: Pathogenicity, Fertility and Toxigenicity - M. Y. Abdalla; A. A. Al-Rokibah; A. Moretti; A. Logrieco (Cereal Research Communications, 1997)

Chelation therapy and the tissue distribution and excretion of lead in mice - Elsie M. B. Sorensen; Elizabeth S. Moretti; Arthur Lindenbaum (Archives of Environmental Contamination and Toxicology, 1980)